2005
DOI: 10.1152/japplphysiol.00361.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery smooth muscle activation attenuates arterial dysfunction during acute pulmonary hypertension

Abstract: Armentano. Pulmonary artery smooth muscle activation attenuates arterial dysfunction during acute pulmonary hypertension. J Appl Physiol 98: 605-613, 2005. First published October 15, 2004 doi:10.1152/ japplphysiol.00361.2004.-Acute pulmonary hypertension (PH) may arise with or without an increase in vascular smooth muscle (VSM) tone. Our objective was to determine how VSM activation affects both the conduit (CF) and wall buffering (BF) functions of the pulmonary artery (PA) during acute PH states. PA instant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…We have previously shown that proximal PA vasoconstriction induced by vascular smooth muscle activation improves both buffering and conduit function of the PA during acute PH mainly due to the increase in wall viscosity, preventing increased wall stiffness secondary to the recruitment of collagen fibers [23]. This different response to levosimendan could be linked to the differential distribution of electrophysiologically distinct smooth muscle cells in CPAs and RPAs arteries [1].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that proximal PA vasoconstriction induced by vascular smooth muscle activation improves both buffering and conduit function of the PA during acute PH mainly due to the increase in wall viscosity, preventing increased wall stiffness secondary to the recruitment of collagen fibers [23]. This different response to levosimendan could be linked to the differential distribution of electrophysiologically distinct smooth muscle cells in CPAs and RPAs arteries [1].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the relation between pulsatility and hemodynamic variables, described in some studies, suggests that the changes in pulmonary vessel remodeling may be responsible for the functional alterations shown by IVUS. It has already been reported that only indexes relating pressure and diameter followed qualitative changes of the elastic incremental modulus (a true evaluator of the elastic status of the vessel wall from the stress-strain relationship) in an animal model of acute PH [29] . Rodés-Cabau et al [30] demonstrated PA wall abnormalities in all patients with primary PH, mostly eccentric.…”
Section: Partitioning Of Pulmonary Vascular Impedance In Phmentioning
confidence: 99%
“…The correct position of the ultrasonic crystals was confirmed at necropsy. All procedures were performed like in previous work [2], [28], [29], [30], [31], [32], [33], [34], [35].…”
Section: ) Surgical Preparation and Segment's Acquisitionmentioning
confidence: 99%
“…Finally, a non-constricting ultrasonic perivascular flow probe (Model T206, Transonic Systems Inc., Ithaca, NY, USA) was positioned around each artery. The technique described has been used by members of our group both in in vivo [2], [30], [31], [32] and in vitro studies [28], [29], [33], [34], [35].…”
Section: ) Surgical Preparation and Segment's Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation